2016
DOI: 10.18632/oncotarget.7287
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between RON and androgen receptor signaling in the development of castration resistant prostate cancer

Abstract: Castrate-resistant prostate cancer (CRPC) is the fatal form of prostate cancer. Although reactivation of androgen receptor (AR) occurs following androgen deprivation, the precise mechanism involved is unclear. Here we show that the receptor tyrosine kinase, RON alters mechanical properties of cells to influence epithelial to mesenchymal transition and functions as a transcription factor to differentially regulate AR signaling. RON inhibits AR activation and subset of AR-regulated transcripts in androgen respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 56 publications
(54 reference statements)
3
29
0
Order By: Relevance
“…Furthermore, levels of c‐FLIP are also elevated in human prostate tumors including castrate resistant tumors making it a clinically relevant target. Our findings that increased expression of AR, RON, and c‐FLIP in tumors is in line with published studies including our own . However, the present study to the best of our knowledge is the first report showing a correlation between RON/AR with ethnicity.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, levels of c‐FLIP are also elevated in human prostate tumors including castrate resistant tumors making it a clinically relevant target. Our findings that increased expression of AR, RON, and c‐FLIP in tumors is in line with published studies including our own . However, the present study to the best of our knowledge is the first report showing a correlation between RON/AR with ethnicity.…”
Section: Resultssupporting
confidence: 93%
“…Previously, we showed that RON promotes PCa cell growth by functioning as a transcription factor to activate c-FLIP. 2 We recently demonstrated that RON is activated as an alternative by-pass signaling mechanism to compensate for the loss of AR under androgen-deprived conditions. These data suggest that under androgen-deprived conditions RON activates AR pathway leading to castrate-resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations